Keanekaragaman Bivalvia Laut di Pesisir Pasuruan sebagai Potensi Sumber Belajar Biologi Kelas X SMA - Muthoharoh, Arini (Undiksha, 2023)
This study aims to analyze the structure of the Bivalve community based on diversity and dominance indices in Pasuruan to become a potential learning resource for Biology Class X SMA learning. Bivalves are a phylum of mollusks that have many benefits for the ecosystem. Bivalve research on the coast of Pasuruan village kalirejokecamatan kraton there is still no research and also the lack of contextual learning resources based on local potential so that it supports this research. sampling is done exploratory research with purposive sampling method at each research station using an iron scratching tool. The results of the study found as many as 5 orders of 11 species of Bivalves from the orders Arcoida, Veneroida, Tellinida, Mytilida, and Vilobransia. The Diversity Index of species from the Bivalve Class Mollusc Phylum has a level of diversity that is categorized as moderate on the coast of Pasuruan with a diversity index value of 1.563. The Dominance Index of species from the Bivalve Class Molluscs has a dominance level that is categorized as low on the coast of Pasuruan with a dominance index value of 0.27. The results of the analysis of the relationship between Bivalve community structure research and Biology learning in the independent curriculum, has the potential to be found in Phase E Learning Outcomes, class X SMA biodiversity material. The results of the identification of these linkages will be poured into teaching materials in the form of Modules and Handouts and practicum guides.